Preparation of Pickering Emulsion Stabilized by Cellulose Nanocrystals and Gelatin and Their Emulsification Characteristics - Lin LIU; Dan WANG; Qian ZHANG; Yuxian LONG; Jie TANG; Xingzhong ZHANG (Shipin gongye ke-ji)
Cellulose nanocrystals (CNC) are rod-shaped, nanoscale colloidal particles. Their strong hydrophilicity and the single functional group structure seriously have limited potential utilization in stabilizing Pickering emulsions. This study aimed to improve the emulsification ability of CNC to prepare more stable emulsions. CNC and gelatin protein (GE) were combined to form complex colloidal particles, and subsequently stabilizing oil phase to fabricate stable O/W Pickering emulsions. The effects of different pH and compound ratios on the properties of CNC/GE complexes were characterized and analyzed using Zeta potential, turbidity, and Fourier transform infrared spectroscopy (FTIR). The characteristics of the obtained Pickering emulsions were investigated by morphology observation, particle size and distribution experiments. The results indicated that the CNC/GE complex colloidal particles were formed by electrostatic interaction at pH4.2, which presented excellent emulsification performance and thermal stability. With the increasing content of GE in the CNC/GE complexes, the particle size of obtained complex particles gradually decreased. When the ratio of CNC to GE in the complex was 1:5, the particle size was 305.3 nm, and when the ratio was 1:9, the particle size reduced to 258.3 nm. And their thermal stability were improved. Meanwhile, the resultant Pickering emulsions had the smaller and more uniform droplet sizes, and exhibited the enhanced storage stability. This research provides a theoretical basis for expanding the applications of cellulose/protein complexes in food-grade Pickering emulsions.